Characterization of vaginal exfoliative cytology in alpacas (Vicugna pacos) - Pacheco, Joel (2017)
The characterization of the cellular forms found in vaginal smears of non-pregnant alpacas was carried out, as well as the characterization of the maturation index in various physiological stages (non-pregnant, pregnant, early post-partum, post-copula) and the description of the vaginal tissue of non-pregnant and pregnant females to determine structural differences. Differences in the maturation index between non-pregnant and pregnant alpacas could be useful as a diagnostic method of gestation.